Time truncated generalized chain sampling plan for pareto distribution of the 2nd kind - Razzaque Mughal, Abdur; Zain, Zakiyah; Aziz, Nazrina (MAXWELL Science Publication, 2015)
The main purpose of this study is to intend a generalized chain sampling plan for Pareto distribution of the 2nd kind.The designed parameters such as the minimum sample size and operating characteristic values are found by satisfying the consumer's risk at the specified quality levels in terms of average. The results are explained by an example.